Prevalence and predictors for unintended pregnancy among HIV-infected pregnant women in Lira, Northern Uganda: a cross-sectional study - Napyo, Agnes (Sci Rep, 2020)
Prevention of unintended pregnancies is a global strategy to eliminate mother-to-child transmission of HIV. Factors surrounding unintended pregnancy among women living with HIV are not well understood. We aimed to determine the prevalence and predictors for unintended pregnancy among these women in Northern Uganda. We conducted a cross-sectional survey among 518 women using a structured questionnaire. We asked questions on socio-demographic, reproductive-related and HIV-related characteristics. We conducted multivariable logistic regression and reported adjusted odds ratios. The prevalence of unintended pregnancy was 41.1%. The predictors for unintended pregnancy were: being single (not living with a partner or being in a marital union), having five or more children and taking antiretroviral drugs for long periods of time. HIV counselling services should target women living with HIV who are not in a marital union, those having a higher parity and those who have taken ART for longer periods.